Synthesis of Sr6LuAl(BO3)6:Sm3+ Red Phosphor with Excellent Thermal Stability and Its Application in w-LEDs - Anlin Zhang; Yue Yang; Yuqing Peng; Hao Zhou; Wei Tang; Jianhong Jiang; Yiting Wu; Shiying Cai; Lianwu Xie; Bin Deng (Molecules)
In this study, a series of Sr6LuAl(BO3)6:Sm3+ red phosphors were successfully prepared with a high-temperature solid-phase technology. The Rietveld refinement analysis of the X-ray diffraction (XRD) diffraction patterns indicated that the as-prepared phosphors belong to the <semantics>R<mover accent="true">3¯</mover></semantics> space group of the hexagonal crystal system. Under 404 nm near-ultraviolet excitation, the Sr6LuAl(BO3)6:Sm3+ phosphor exhibits narrowband emission within the range of 550 to 750 nm. The primary emission peak is observed at a wavelength of 599 nm, corresponding to 6H5/2 → 4F7/2. The optimum doping concentration of the Sr6LuAl(BO3)6:xSm3+ phosphor is 10 mol%. Nearest-neighbor ion interaction is the mechanism of concentration quenching. The synthesized phosphors demonstrate exceptional thermal stability, with a high quenching temperature (T0.5 > 480 K). Furthermore, the assembled white light-emitting diode (w-LED) device exhibits a low color temperature (5464 K), an excellent color rendering index (Ra = 95.6), and CIE coordinates (0.333, 0.336) close to those of standard white light. Collectively, these results suggest the enormous potential of Sr6LuAl(BO3)6:Sm3+ phosphors for applications in w-LEDs.